Corrosion and Inhibitor Evaluation of N80 Steel in Medium and High Temperature H2S Environment - SUN Yu - bao, WANG Shao - hua, XIAO Sa, JI Hui (Cailiao Baohu, 2021)
Associated H2S was found in offshore thermal flooding oil production, which brought corrosion and safety hazards to production tubing. In order to analyze the corrosion characteristics and protect against corrosion, autoclave weightlessness method and scanning electron microscope were employed to analyze the corrosion behavior of N80 steel in the produced water of medium and high temperature H2S - containing oil wells. Moreover, the effects of flow rate and H2S partial pressure were discussed, and suitable H2S corrosion inhibitors were screened and evaluated. Results showed that the corrosion of N80 steel in produced water containing H2S was more serious, and the corrosion rate was the highest at 80 ℃; with the increase of H2S partial pressure and flow rate, the corrosion rate increased rapidly. After corrosion, there were black ferrosulfides on the surface of the steel, and the surface products were loose and incomplete. All of different corrosion inhibitors added could inhibit corrosion. Among them, the corrosion inhibitor CI - S - 11 possessed the optimal effect, and its corrosion inhibition rate exceeded 85%, which could be used for on - site tubing protection.